2007
DOI: 10.1038/sj.mt.6300067
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 and Parkin Modulate Dopamine-dependent Behavior and Inhibit MPTP-induced Nigral Dopamine Neuron Loss in Mice

Abstract: Parkin-deficient animals exhibit mitochondrial degeneration and increased oxidative stress vulnerability, and both mice and flies lacking DJ-1 are hypersensitive to environmental toxins associated with Parkinson's disease (PD). We used recombinant adeno-associated virus (AAV) gene transfer to study the influence of DJ-1 and Parkin on the dopaminergic system of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice, a model for sporadic PD. After MPTP lesioning, significantly more dopamine neurons sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 46 publications
8
73
0
1
Order By: Relevance
“…Also, overexpression of DJ-1 reduced postsynaptic dopamine receptor responses in normal mice. These results suggest that further exploration of the molecular functions of DJ-1 for in vitro and in vivo is warranted before DJ-1 therapy for PD can commence (Paterna et al, 2007). In agreement with our results, transduced Tat-DJ-1 protein markedly decreased MPTP-induced TH neuron loss in mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, overexpression of DJ-1 reduced postsynaptic dopamine receptor responses in normal mice. These results suggest that further exploration of the molecular functions of DJ-1 for in vitro and in vivo is warranted before DJ-1 therapy for PD can commence (Paterna et al, 2007). In agreement with our results, transduced Tat-DJ-1 protein markedly decreased MPTP-induced TH neuron loss in mice.…”
Section: Discussionsupporting
confidence: 90%
“…However, the precise mechanisms remain to be studied further. Paterna et al (2007) has shown that overexpression of DJ-1 significantly reduces MPTP-induced TH neuron loss in mice. Although the mechanism is unclear, overexpression of DJ-1 may reduce DAT functions which contribute to the increased resistance of DJ-1 expression dopamine neurons against MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85] Furthermore, viral vector-mediated PARK2 delivery prevents dopamine neuron loss induced by 6-OHDA and MPTP. 86,87 These findings taken together suggest that PARK2 delivery may be therapeutically beneficial not only in familial PD patients but also in sporadic PD.…”
Section: Transfer Of Disease Genesmentioning
confidence: 92%
“…Down-regulation of DJ-1 has been shown to increase the susceptibility to oxidative stress and proteasome inhibition [91,92].DJ-1 also acts as a redoxdependent chaperone molecule and inhibits α-synuclein aggregation [93]. Over-expression of DJ-1 protects against MPTP-induced neurodegeneration, indicating that the augmented expression of DJ-1 in response to the toxins is probably a helpful mechanism in fighting against the increased oxidative stress [94,95]. Knockout models of DJ-1 mice with a targeted deletion of exon 2 or insertion of a premature stop codon in exon 1 are more sensitive to toxins and oxidative stress.…”
Section: Dj-1 Gene Modelmentioning
confidence: 99%